Fusion under the Scope: Minimally Invasive Arthroscopic Tibiotalocalcaneal Arthrodesis in the Setting of Post-traumatic Fibular Loss: A Case Report - Prashant Pawar; Satyam Jawa; Vishal Patil (Journal of Orthopaedic Case Reports)
Introduction: Arthroscopic tibiotalocalcaneal (TTC) arthrodesis with intramedullary nail fixation is a minimally invasive technique for managing complex hindfoot pathologies, especially in patients with soft tissue injuries or poor skin conditions after trauma. Case Report: We present the case of a 44-year-old male farmer with post-traumatic instability over his left ankle and soft tissue injury over the lateral aspect of his left lower limb secondary to a degloving injury involving a runover by a tractor. The patient had previously undergone debridement with an anterolateral thigh flap for wound coverage 3 months ago. Examination revealed severe mediolateral instability, complete distal one-third fibular loss with severe functional impairment. An arthroscopically assisted TTC fusion using a retrograde intramedullary nail was performed. The technique allowed precise joint preparation, strong internal fixation, and minimized soft tissue disruption. Post-operatively, the patient achieved a stable, plantigrade, and pain-free foot with early mobilization and improved functional outcomes, as evidenced by a high American Orthopaedic Foot and Ankle Society score and Foot and Ankle Disability Index score. Conclusion: This case demonstrates that arthroscopic TTC nailing can be a safe and effective solution in complex clinical scenarios, offering advantages, such as reduced risk of post-operative infections, earlier rehabilitation, quicker wound healing, and satisfactory limb alignment. Despite promising results, further research and long-term studies are needed to validate this technique across broader patient populations and establish standardized surgical protocols.